COVID Arm: Delayed Hypersensitivity Reactions to SARS-CoV-2 Vaccines Misdiagnosed as Cellulitis - Aleksandra L. Lindgren; Andrea Hui Austin; Kathleen M. Welsh (SAGE Publishing, 2021)
The term "COVID arm" has been coined to describe a harmless delayed hypersensitivity reaction occurring approximately a week after administration of the novel SARS-CoV-2 mRNA vaccine. It appears as a red, warm, pruritic, indurated, or swollen area in the vicinity of the vaccine site. These reactions, especially if accompanied by systemic symptoms, have been mistaken for cellulitis. We report 3 cases of COVID arm, 2 of which were mistaken for cellulitis. Distinguishing features of COVID arm from cellulitis include pruritus as a common finding, occurrence approximately a week after vaccination, a lack of progression of symptoms, rapid response to topical steroids, and/or spontaneous resolution usually over 4 to 5 days. Practice Points: • Patients receiving SARS-CoV-2 vaccines may experience delayed hypersensitivity reactions characterized by erythema, swelling, and itching occurring near the vaccination site (COVID arm), approximately a week after vaccination. • Clinicians can distinguish SARS-CoV-2 vaccine reactions from cellulitis by the time of onset (approximately a week vs 5 days), by the lack of progression of symptoms, and resolution over 4 to 5 days. • Severe cases of COVID arm may be treated with topical steroids.